An Improved Genetically Encoded Fluorescent cAMP Indicator for Sensitive cAMP Imaging and Fast Drug Screening - Liu, Wenfeng; Liu, Chang; Ren, Pei-Gen; Chu, Jun; Wang, Liang (Frontiers in Pharmacology, 2022)
Cyclic adenosine 3’,5’-monophosphate (cAMP) is an important intracellular second messenger molecule downstream of many G protein-coupled receptors (GPCRs). Fluorescence imaging with bright and sensitive cAMP indicators allows not only dissecting the spatiotemporal dynamics of intracellular cAMP, but also high-content screening of compounds against GPCRs. We previously reported the high-performance circularly permuted GFP (cpGFP)-based cAMP indicator G-Flamp1. Here, we developed improved G-Flamp1 variants G-Flamp2 and G-Flamp2b. Compared to G-Flamp1, G-Flamp2 exhibited increased baseline fluorescence (1.6-fold) and larger fluorescence change (ΔF/F0) (1300% vs. 1100%) in HEK293T cells, while G-Flamp2b showed increased baseline fluorescence (3.1-fold) and smaller ΔF/F0 (400% vs. 1100%). Furthermore, live cell imaging of mitochondrial matrix–targeted G-Flamp2 confirmed cytosolic cAMP was able to enter the mitochondrial matrix. G-Flamp2 imaging also showed that adipose tissue extract activated the Gi protein-coupled orphan GPCR GPR50 in HEK293T cells. Taken together, our results showed that the high-performance of G-Flamp2 would facilitate sensitive intracellular cAMP imaging and activity measurement of compounds targeting GPCR-cAMP signaling pathway during early drug development.